(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Waqf is an instrument in Islamic economics that has the potential to improve people’s welfare and overcome the problem of poverty. Waqf has two sides to the relationship, namely the relationship to God and also the relationship to humans/muammalah. The purpose of this research is to get issues related to waqf governance. The findings show that the waqf assets are still dominant in 3M (Masjid/Mosque, Mushola/prayer room, and Makam/the grave) and the management of waqf assets in Indonesia still does not lead to economic empowerment because most of the waqf is still mostly of consumptive waqf. The solution is Nazir must implement good management by implementing the principles of Good Waqf Governance, including the principles of accountability and accountability, candor, fairness, and independence. through the role of waqf governance, traditional waqf management will shift towards productive waqf management so that the contribution will be greater and have an impact on the optimization of waqf assets managed by Nazhir in Indonesia. The more productive endowments will ultimately have implications for the welfare of society and the economy in Indonesia.